Multi-Agent Maritime Traffic Simulator - Luka Grgicevic (Modeling, Identification and Control)
This simulator is designed to support research on centralised game-theoretical algorithms for maritime traffic management. It supports an arbitrary number of vessels and land masses import. Vessels are modelled as agents whose motion is governed by the kinematic equations and the land masses are polygon shape files. In the simulator, each vessel has access to the reward oracle, which evaluates the agents' strategies by taking into account the risk of collision and grounding, the level of compliance with the traffic rules and the operational efficiency. A game-theoretical model predictive control then generates optimal trajectories for every traffic participant simultaneously. Vessels are engaged in repeated competitive polymatrix games, whose equilibria solutions are a series of waypoints, meant to be broadcast as navigational decision support by the Vessel Traffic Services. We convey the agents' and functions' modelling principle implemented in NetLogo and present the overall simulator structure and scope.